2013
DOI: 10.1016/j.bodyim.2013.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the role of gender in body image research settings: Participant gender preferences for researchers and co-participants in interviews, focus groups and interventions

Abstract: Participant gender preferences for body image researchers, interventionists and focus group and intervention co-participants have been largely ignored, despite recognition that such characteristics can influence the nature and quality of data collected and intervention effects.To address this, Australian women (n = 505) and men (n = 220) completed a questionnaire about their preferences for interviewers and focus group facilitators, for teachers delivering school-based interventions, and for co-participants in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…Being a female researcher may have benefited my interactions when discussing body image with the women in my study due to shared experiences (e.g., female body objectification). Interestingly, men have been found to be equally or even more likely to disclose body image concerns to a female researcher as opposed to a male researcher (Yager, Diedrichs, & Drummond, 2013). Therefore, my gender may not have impeded the men's willingness to disclose their body image concerns.…”
Section: Retrospective Reflexivitymentioning
confidence: 96%
“…Being a female researcher may have benefited my interactions when discussing body image with the women in my study due to shared experiences (e.g., female body objectification). Interestingly, men have been found to be equally or even more likely to disclose body image concerns to a female researcher as opposed to a male researcher (Yager, Diedrichs, & Drummond, 2013). Therefore, my gender may not have impeded the men's willingness to disclose their body image concerns.…”
Section: Retrospective Reflexivitymentioning
confidence: 96%
“…Reviewing mainly health promotion programmes [ 37 ] has revealed overall small to medium effect sizes for studies focusing on media literacy, self-esteem and the influence of peers. More recent studies indicate that actively promoting a positive body image increases physical activity level, decreases DE, dieting, alcohol consumption and cigarette use [ 38 , 39 ] and that a mindful, non-judgmental and compassionate attitude to one’s body may protect against self-objectification and a negative body image [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interviews were conducted by the primary researcher who is female, and it may be challenging for men to be forthcoming with information about their sexuality with a researcher of the opposite sex. However, it has been reported that men are equally, if not more likely, to reveal concerns related to body image with a female researcher (Yager, Diedrichs, & Drummond, 2013) and that a female interviewer is generally preferred. Possible explanations may be related to social norms and expectations that women would naturally be more sympathetic (Pollner, 1998) and less critical (Derlega, Winstead, Wong, & Hunter, 1985).…”
Section: Discussionmentioning
confidence: 99%